Development of phosphorus-doped noble metal (Pt, Pd) electrocatalysts for selective oxidation of glycerol to value added chemicals - Muhammad Sheraz, Ahmad (2020)
Glycerol is a by-product of biodiesel obtained during transesterification of the vegetable oil (one kg in every 10 kg of biodiesel). Its improper handling can create environmental issues. Much work has been devoted to the transformation of glycerol by various catalytic processes involving reforming, oxidation, hydrogenolysis, etherification, esterification and so on. It can be converted into various valuable chemicals, such as dihydroxyacetone (DHA), glyceraldehyde (GALD), mesoxalic acid (MOXA), glyceric acid (GLY), tartronic acid (TAT), and oxalic acid (OXA) by using different chemo-catalytic and electrocatalytic techniques. Main target of all these techniques is to achieve efficient and economical conversion of glycerol to desired products with highest selectivity. Glycerol electro-oxidation reaction (GOR) could offer potentially safe, non-hazardous and sustainable method to produce value-added products from glycerol. In this work, the effect of noble metals (Pt & Pd) and non-metals modified nanoparticles (P-doped Pt, Pdoped Pd) supported over multiwalled carbon nanotubes in three electrode cell system is reported for electro-oxidation of glycerol. As prepared catalysts were physicochemically characterized by Brunauer-Emmett-Teller (BET), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Field emission electron spectroscopy (FESEM), energy-dispersive X-ray spectroscopy (EDX) and Transmission electron microscopy (TEM) to get better insight about the effect of specific surface area, crystallite size, particle size, and oxidation states of doped non-noble metal on performance of electrocatalysts for GOR. The electrochemical properties of the catalysts were measured through cyclic voltammetry and chronoampermetry using a potentiostat and HPLC was used to analyze and quantify the GOR products. Initial studies found that the Pt/CNT and Pd/CNT electrocatalysts with a particle size of about 4.2 nm and 5.13 nm respectively was prepared by using hydrazine reduction method. It was demonstrated a high durability, electrochemical activity can achieve product selectivity of 90-95% for selective synthesis of tartronic acid in alkaline media. Bi-metallic (Pt-Pd/CNT) electrocatalysts showed higher electrochemical surface area (322.0 m2/g), and selectivity of mesoxalic acid (87%). Although noble metals proved to be promising catalyst with high selectivity but due to commercial constraints of costly noble metals, incorporation of non-metal (P) was chosen as best method to solve this problem. Since, homogeneity of non-metals remains a problem, so in this work, P-doped Pt/CNT and P-doped Pd/CNT were prepared using hydrothermal method with a diameter of 6.23 nm and 3.7 nm were obtained. The results showed superior ECSA (335.95 m2/g & 392.22 m2/g, respectively) than previously mentioned noble metal catalysts. In addition, DHA and tartronic acid selectivity of 90.82% and 47% respectively was obtained. It was found that all the Pd catalyst (Pd/CNT & P-doped Pd) showed higher current density, lower onset potential, high ECSA, narrow particle size, high selectivity for desired products and better resistance (If/Ib =2.37) as compared to Pt catalysts confirming the higher catalytic activity of these catalysts. The results of P-doping into Pt and Pd suggested that addition of phosphorous (P) not only contributed for high activity but also an economical approach for future commercialization of GOR electrocatalysts. It was also found that the product selectivity remarkably enhanced for doped catalysts showing lowest; onset potential, applied potential along with high; ECSA and current density.